The social conquest of earth - Wilson, Edward (New York : Liveright Publishing Corporation, 2012)
Refashioning the story of human evolution, Edward O. Wilson draws on his remarkable knowledge of biology and social behavior to demonstrate that group selection, not kin selection, is the premier driving force of human evolution. In a work that James D. Watson calls "a monumental exploration of the biological origins of the human condition," Wilson explains how our innate drive to belong to a group is "both a great blessing and a terrible curse" (Smithsonian magazine). Demonstrating that the sources of morality, religion, and the creative arts are fundamentally biological in nature, the renowned Harvard biologist presents us with the clearest explanation ever produced as to the origin of the human condition and why it resulted in our domination of the Earth's biosphere.
I. Why does advanced social life exist? -- II. Where do we come from? -- III. How social insects conquered the invertebrate world -- IV. The forces of social evolution -- V. What are we? -- VI. Where are we going?.
Includes index.
Keywords: SOCIAL EVOLUTION -- PHILOSOPY; HUMAN EVOLUTION -- PHILOSOPY